EFFICIENCY OF THE VINORELBINE – CAPECITABINE + BEVASIZUMAB REGIMEN IN THE TREATMENT OF PATIENTS WITH METASTATIC TRIPLE NEGATIVE BREAST CANCER - Khakimov G. A.; Atakhanova N. E.; Khakimova G. G.; Almuradov A.; Almuradova D. M.; Ziyayev Sh.V.; Ismailov J. Kh (Web of Journals Publishing, 2024)
The most aggressive and unpredictable among the subtypes of breast cancer is triple negative breast cancer, which has high proliferative activity and a high growth rate, early leading to damage to internal organs and the central nervous system. In the presence of distant metastases, the median overall survival does not exceed 14 months. TNBC is an extremely heterogeneous group of tumors; it includes both tumors that are highly sensitive to chemotherapy and those that require targeted or immunotherapy to achieve the best treatment results. The heterogeneity of the group of triple negative breast cancer and the absence of conventional molecular targets for drug action (hormone receptors and HER-2/ neu amplification ) explain the difficulties in choosing treatment tactics. Such subtype features make it difficult to develop a uniform treatment strategy for all patients. Current understanding of resistance mechanisms and molecular drivers of progression has expanded therapeutic options for metastatic TNBC ( mTNBC ). All this indicates the need to develop new antitumor therapy regimens that are not typical for other forms of breast cancer, which will improve the results of treatment for such patients.
Keywords: triple negative breast cancer, chemotherapy, metastasis, target therapy.